Gambaran Status Gizi Pada Siswa(i) SD Negeri 100 Kendari - Fithria Fithria; Najwa Namrin; Ayu Anisa Putri A; Rahayanah Rahayanah; Iin Mutmaina; Wa Ode Umalia; Sinar Dwi Ulfa; Dela Ramadhan (Jurnal Kendari Kesehatan Masyarakat, 2025)
This study aims to evaluate the nutritional status of students at SD Negeri 100 Kendari, considering the importance of good nutrition for children's growth and development. Using quantitative descriptive methods, this research involved 40 respondents aged 9-12 years, with nutritional status measurement carried out through Body Mass Index (BMI) analysis based on Ministry of Health guidelines. The research results showed that 67.5% of respondents had normal nutritional status, while 20% were categorized as underweight, 7.5% overweight and 5% obese. Even though the majority of children are in the good nutritional category, there are still children who are at risk of experiencing long-term health problems due to less than optimal nutritional status. This research emphasizes the importance of sustainable interventions to increase public awareness about healthy eating patterns and physical activity to support optimal growth and development of children